Digital Infidelity, Women's Defamation, and Patriarchal Reproduction: Gender Reconstruction Through Critical Discourse Analysis and Mubādalah of Narrative on Instagram Accounts - Zarroq, Sulthan Aufa; Iffah, Iffah; Muktafi, Muktafi (LPPM IAIN Kudus, 2026)
This study analyzes the construction of digital religious discourse regarding infidelity and the narrative of